A Solution‐Processable meso‐Phenyl‐BODIPY‐Based n‐Channel Semiconductor with Enhanced Fluorescence Emission. Issue 9 (26th June 2019) - Ozcan, Emrah; Ozdemir, Mehmet; Ho, Dongil; Zorlu, Yunus; Ozdemir, Resul; Kim, Choongik; Usta, Hakan; Cosut, Bunyemin
Abstract: The molecular design, synthesis, and characterization of an acceptor‐donor‐acceptor (A‐D‐A) semiconductor BDY‐Ph‐2T‐Ph‐BDY comprising a central phenyl‐bithiophene‐phenyl π‐donor and BODIPY π‐acceptor end‐units is reported. The semiconductor shows an optical band gap of 2.32 eV with a highly stabilized HOMO/LUMO (−5.74 eV/−3.42 eV). Single‐crystal X‐ray diffraction (XRD) reveals D–A dihedral angle of ca. 66° and strong intermolecular "C−H ⋅⋅⋅ π (3.31 Å)" interactions. Reduced π‐donor strength, increased D–A dihedral angle, and restricted intramolecular D–A rotations allows for both good fluorescence efficiency (ΦF =0.30) and n ‐channel OFET transport (μ e =0.005 cm 2 /V ⋅ s; Ion /Ioff =10 4 –10 5 ). This indicates a much improved (6‐fold) fluorescence quantum yield compared to the meso ‐thienyl BODIPY semiconductor BDY‐4T‐BDY. Photophysical studies reveal important transitions between locally excited (LE) and twisted intramolecular charge‐transfer (TICT) states in solution and the solid state, which could be controlled by solvent polarity and nano‐aggregation. This is the first report of such high emissive characteristics for a BODIPY‐based n ‐channel semiconductor. Abstract : Rational design for enhanced fluorescence : The realization of a phenyl–bithiophene–phenyl acceptor‐donor‐acceptor (A‐D‐A) semiconductor demonstrates that combining good fluorescence emission (6‐fold enhanced Φ F ) and n ‐channel semiconductivity is possible through rational molecular design. Solvent polarity/nano‐aggregation induce remarkable transitions between locally excited (LE) and twisted intramolecular charge‐transfer (TICT) states.